Upregulated Expression of Indoleamine 2, 3-Dioxygenase in Primary Breast Cancer Correlates with Increase of Infiltrated Regulatory T Cells In Situ and Lymph Node Metastasis - Jinpu Yu; Jingyan Sun; Shizhen Emily Wang; Hui Li; Shui Cao; Yizi Cong; Juntian Liu; Xiubao Ren (Clinical and Developmental Immunology)
IDO has been reported to induce immunotolerance and promote metastasis in solid malignancy, but the mechanisms involved were not fully understood. In this study, the expression of IDO in primary breast cancer was examined and the correlation between the expression levels of IDO and the densities of Foxp3+ Tregs in situ was studied. The IDO stably-expressing CHO cells(IDO/CHO) were generated to evaluate the induction of Foxp3+ Tregs after coculturing with CD3+ T cells in vitro. The IDO expression in cancer was higher than that in benign diseases both at RNA and protein levels. The IDO expression was significantly upregulated in tumors of more advanced stages and with more extensive lymph node metastasis, and displayed positive linear correlation with the density of Foxp3+ Tregs. We further demonstrated that CD4+CD25+CD127− Tregs could be amplified by coculturing CD3+ T cells with IDO/CHO cells in vitro which displayed increasing Foxp3 expression both at mRNA and protein levels. Our results implied that up-regulation of IDO in primary breast cancer may inhibit local immune surveillance and promote metastasis by favoring development and infiltration of Foxp3+ Tregs in the tumor microenvironment.